Biohythane production from marine macroalgae Sargassum sp. coupling dark fermentation and anaerobic digestion. (August 2015) - Costa, José C.; Oliveira, João V.; Pereira, Maria A.; Alves, Maria M.; Abreu, Angela A.
Highlights: Biohythane production from Sargassum sp. is feasible and has a high potential. Hydrogen yield of 91.3 ± 3.3 L H2 per kg (VS) of Sargassum sp. was attained. It was achieved a methane yield of 541 ± 10 L CH4 per kg (VS) of Sargassum sp. Potential energy production from Sargassum sp. was estimated in 242 GJ ha −1  yr −1 . The value of estimated energy could result in 600 EJ yr −1 . Abstract: Potential biohythane production from Sargassum sp. was evaluated in a two stage process. In the first stage, hydrogen dark fermentation was performed by Caldicellulosiruptor saccharolyticus . Sargassum sp. concentrations (VS) of 2.5, 4.9 and 7.4 g L −1 and initial inoculum concentrations (CDW) of 0.04 and 0.09 g L −1 of C. saccharolyticus were used in substrate/inoculum ratios ranging from 28 to 123. The end products from hydrogen production process were subsequently used for biogas production. The highest hydrogen and methane production yields, 91.3 ± 3.3 L kg −1 and 541 ± 10 L kg −1, respectively, were achieved with 2.5 g L −1 of Sargassum sp. (VS) and 0.09 g L −1 of inoculum (CDW). The biogas produced contained 14–20% of hydrogen. Potential energy production from Sargassum sp. in two stage process was estimated in 242 GJ ha −1  yr −1 . A maximum energy supply of 600 EJ yr −1 could be obtained from the ocean potential area for macroalgae production.